Mesoporous FeP/RGO nanocomposites as anodes for sodium ion batteries with enhanced specific capacity and long cycling life. (25th March 2020) - Li, Qun; Yuan, Jianjun; Tan, Qinglong; Wang, Guixiang; Feng, Shuai; Liu, Qing; Wang, Qingzhao
Abstract : FeP/RGO nanocomposites were synthesized by a simple precipitation reaction route and low temperature phosphorization strategy, indicating a good sodium ion storage performance. Abstract : In order to improve the specific capacity and cyclability of the iron phosphide (FeP) anode material, mesoporous iron phosphide/reduced graphene oxide (FeP/RGO) nanocomposites were synthesized by a simple precipitation reaction process and low temperature phosphorization technology. FeP nanoparticles with a diameter of about 10–15 nm were uniformly loaded on hierarchical RGO nanosheets. When used as the anode for sodium ion batteries, the FeP/RGO nanocomposite electrode exhibits a high reversible specific capacity of about 547 mA h g −1 at a current density of 100 mA g −1 after 100 cycles. A stable long cycling capacity of about 311 mA h g −1 can also be obtained at a high current density of 1 A g −1 after 1000 cycles. The synergistic interaction between FeP nanoparticles and RGO improved the electrochemical performance of the electrode materials greatly. The outstanding sodium ion storage performance of the FeP/RGO nanohybrid electrode can be attributed to the hierarchically porous structure, good electrical conductivity, and small size effect of the nanoparticles.